Gold nanoclusters-catalyzed rhodamine 6G–K3Fe(CN)6 chemiluminescence and its application. Issue 39 (22nd September 2016) - Yang, Dongqin; He, Yanyan; Sui, Yanyan; Chen, Funan
Abstract : An ultra-facile flow injection chemiluminescence (CL) strategy was designed for bisphenol A (BPA) detection. Abstract : An ultra-facile flow injection chemiluminescence (CL) strategy was designed for bisphenol A (BPA) detection. It was based on the inhibition of rhodamine 6G chemiluminescence by BPA on the gold nanoclusters (Au NCs) enhanced rhodamine 6G–K3 Fe(CN)6 system in an alkaline medium for the first time. Furthermore, BSA-stabilized Au NCs were synthesized via a simple method with desirable reproducibility and stability. Under optimized conditions, the relative CL intensity was found to be proportional to the BPA concentration in the range of 2.0 × 10 −7 to 1.0 × 10 −5 mol L −1, with a detection limit of 7.0 × 10 −8 mol L −1 (S/N = 3). The effects of interfering substances on the detection of 1.0 × 10 −6 mol L −1 BPA were analyzed for confirming good selectivity. A brief discussion on the possible CL reaction mechanism was presented through the results of CL spectra, fluorescent spectra, UV-visible spectroscopy and radical scavenger reactions. Finally, this suggested method was used successfully to detect BPA in real samples with acceptable recovery values of 93.0–106.2%.